Lost in Translation: The Gap in Scientific Advancements and Clinical Application - Fernandez-Moure, Joseph S. (Frontiers in Bioengineering and Biotechnology, 2016)
The evolution of medicine and medical technology hinges on the successful translation of basic science research from the bench to clinical implementation at the bedside. Born out of the increasing need to facilitate the transfer of scientific knowledge to patients, translational research has emerged. Significant leaps in improving global health such as antibiotics, vaccinations, and cancer therapies have all seen successes under this paradigm yet today it has become increasingly difficult to realize this ideal scenario. As hospital revenue demand increase, and financial support declines, clinician protected research time has been limited. Researchers, likewise, have been forced to abandon time and resource consuming translational research to focus on publication generating work to maintain funding and professional advancement. Compared to the surge in scientific innovation and new fields of science have surged, realization of transformational scientific findings in device development and materials sciences has significantly lagged behind. Herein, we describe: how the current scientific paradigm struggles in the new health-care landscape; the obstacles met by translational researchers; and solutions, both public and private, to overcoming those obstacles. We must rethink the old dogma of academia and reinvent the traditional pathways of research in order to truly impact the health-care arena and ultimately those that matter most: the patient.